Diet-induced obesity suppresses ghrelin in rat gastrointestinal tract and serum - Sahin, Ibrahim; Aydin, Suleyman; Ozkan, Yusuf; Dagli, Adile Ferda; Akin, Kadir Okhan; Guzel, Saadet Pilten; Ozercan, Mehmet Resat (Springer, 2011)
The aims of the present study were to examine ghrelin expression in serum and gastrointestinal tract (GIT) tissues, and to measure tissue ghrelin levels and obesity-related alterations in some serum biochemical variables in rats with diet-induced obesity (DIO). The study included 12 male rats, 60 days old. The rats were randomly allocated to two groups (n = 6). Rats in the DIO group were fed a cafeteria-style diet to induce obesity, while those in the control group were fed on standard rat pellets. After a 12 week diet program including an adaptation period all rats were decapitated, tissues were individually fixed, ghrelin expression was examined by immunohistochemistry , and tissue and serum ghrelin levels were measured by radioimmunoassay. Serum biochemical variables were measured using an autoanalyzer. When the baseline and week 12 body mass index and GIT ghrelin expression were compared between DIO and control rats, BMI had increased and ghrelin expression decreased due to obesity. The RIA results were consistent with these findings. Serum glucose, LDL cholesterol, and total cholesterol levels were elevated and HDL cholesterol significantly decreased in the DIO group. A comparison of GIT tissues between the control and obese groups demonstrated that ghrelin was decreased in all tissues of the latter. This decrease was brought about a decline in the circulating ghrelin pool. This suggests that rather than being associated with a change in a single tissue, obesity is a pathological condition in which ghrelin expression is changed in all tissues.
Keywords: Diet-induced obesity; Immunohistochemistry; Gastrointestinal tract; Acylated ghrelin; Desacylated ghrelin